Diagnostic Procedure: Mapping Sentinel Lymph Nodes among Patients with Skin Melanoma - Marko Vlacic; Mirela Eric; Mladen Jovanovic; Sandra Jelcic; Ivan Besenji; Ivana Smiljanic (Disease and Health Research: New Insights Vol. 2, 2024)
Lymph drainage from the skin varies from patient to patient, sometimes even when the tumor is in the same location in two different individuals. The pathway of lymph vessels that collect and drain lymph is unpredictable, as are the locations of SLNs. Therefore, clinical predictions of SLN locations are unreliable and imprecise. Preoperative lymphoscintigraphy with small particle radio colloids allows visualization of all these lymph vessels draining lymph to SLNs. Careful diagnostics will enable the localization of all true SLNs, even when these lymph nodes are sometimes outside the usual lymph basin. The network of lymphatic vessels in the skin has been studied for centuries. In 1984, Sappey published an atlas of lymphatic vessels. The discovery of lymphoscintigraphy around 1950 renewed interest in verifying the pathways of lymphatic vessels in patients with skin melanoma. Lymphoscintigraphy quickly became an indispensable technique for mapping sentinel lymph nodes. Detecting sentinel lymph nodes is essential for conducting adequate diagnostics, appropriately staging patients, and administering necessary therapy. Any lymph node that removes lymph from the tumor site is considered a sentinel lymph node. Because lymphatic arteries can pass through that cluster of lymph nodes and empty into other lymph nodes, it might not even be the closest to the tumor location. Patients with cutaneous melanoma have their sentinel lymph nodes mapped with lymphoscintigraphy. It entails administering intradermal injections of a radiocolloid in the region of the excisional biopsy site or in close proximity to the melanoma site. The location of all lymphatics is marked with a marker or tattooed with a dot on the skin above the node. Radiocolloid particles used for sentinel identification are in the size range of 5-50 nanometers. These particles easily enter lymphatic capillaries, and their entry is facilitated by exercise or massage of that body part. The lymphatic drainage of the skin varies from patient to patient, sometimes even when the tumor is in the same location in two different individuals. Therefore, careful diagnostics will enable the location of all true sentinel lymph nodes. Careful diagnostics will enable the localization of all true SLNs, even when these lymph nodes are sometimes outside the usual lymph basin. This is crucial for accurate staging of patients with melanoma.